Profitability Moderates Trading Frequency, Volume, And LQ45 Stock Returns - Musthofa, Rahmawati Hidayatul; Alfita Rakhmayani (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
This study investigates the influence of trading frequency and trading volume on stock returns, with profitability as a moderating variable, in companies listed in the LQ45 Index on the Indonesia Stock Exchange (IDX) from 2021 to 2024. Using secondary data from annual financial reports and stock trading data, this study employs a quantitative research approach with a purposive sampling method, selecting 45 companies listed in the LQ45 index for the period 2021–2024. The data were collected through documentation techniques from the Indonesia Stock Exchange (IDX) and company financial statements. The analysis was conducted using Moderated Regression Analysis (MRA) to examine both direct and moderating effects. The findings reveal that trading frequency has a positive and significant effect on stock returns, while trading volume does not show a significant effect. Profitability is proven to strengthen the positive relationship between trading frequency and stock returns, but does not moderate the relationship between trading volume and stock returns. These results highlight the role of trading activity and company performance in shaping stock returns, providing insights for investors in making investment decisions.